2016
DOI: 10.1007/s11999-016-5009-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel Augmentation Technique for Patellar Tendon Repair Improves Strength and Decreases Gap Formation: A Cadaveric Study

Abstract: Background Patellar tendon ruptures commonly are repaired using transosseous patellar drill tunnels with modified-Krackow sutures in the patellar tendon. This simple suture technique has been associated with failure rates and poor clinical outcomes in a modest proportion of patients. Failure of this repair technique can result from gap formation during loading or a single catastrophic event. Several augmentation techniques have been described to improve the integrity of the repair, but standardized biomechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 35 publications
(76 reference statements)
1
34
0
Order By: Relevance
“…Our results are consistent with those of previous studies that have shown significantly improved gap formation with other augmentation strategies for inferior pole patellar tendon repair. 3 , 5 , 7 At 250 cycles, Ravalin et al. 3 reported significantly greater gap formation with the standard Krackow transosseous technique (7.3 ± 0.5 mm) compared with augmentation with either Ethibond suture (4.9 ± 0.5 mm) or 2.0 Dall-Miles cables (3.5 ± 0.8 mm).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results are consistent with those of previous studies that have shown significantly improved gap formation with other augmentation strategies for inferior pole patellar tendon repair. 3 , 5 , 7 At 250 cycles, Ravalin et al. 3 reported significantly greater gap formation with the standard Krackow transosseous technique (7.3 ± 0.5 mm) compared with augmentation with either Ethibond suture (4.9 ± 0.5 mm) or 2.0 Dall-Miles cables (3.5 ± 0.8 mm).…”
Section: Discussionmentioning
confidence: 98%
“… 2 Several strategies for augmentation of this technique have been studied, including the use of cerclage wires, figure-8 suture, and hamstring autograft. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 These augmented techniques have demonstrated superior biomechanical properties compared with the Krackow transosseous technique alone, which may facilitate advanced biomechanical stability to support accelerated rehabilitation protocols. 3 , 4 , 5 , 6 , 7 , 8…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, primary repair utilizing nonabsorbable sutures to treat this patient's acute patellar tendon injury was decided to be utilized. An important factor taken into consideration was the potential for gap formation with which was previously demonstrated in biomechanical studies of this procedure choice [ 17 , 18 ]. However, it was ultimately decided that the potential benefits outweighed the risks for this procedure in comparison to the other techniques for patellar tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Biological augmentation of primary repair is believed to decrease strain across the repair site and reduce the risk of rerupture. 7 Mihalko et al. 14 performed a matched-pair cadaveric analysis in which primary suture repair was compared with suture repair with hamstring augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have proposed augmentation strategies in an effort to decrease strain across the repair site, allow early knee motion, and reduce the risk of rerupture. 7 Various augmentation techniques have been described including both nonbiological (cerclage wire, synthetic tape, or nonabsorbable suture) and biological (allograft or autograft) augmentation strategies, but the optimal treatment method remains controversial. 8 , 9 , 10 , 11 , 12 We present a technique for primary patellar tendon repair with bidirectional fixation using transosseous tunnels, suture anchor fixation, and ipsilateral hamstring autograft augmentation in a distal patellar pole socket ( Table 1 , Table 2 , Table 3 ).…”
mentioning
confidence: 99%